Energy-based seismic retrofit and design of building frames with passive dampers. (1st January 2022) - Hareen, CH.B.V.; Mohan, S.C.
Graphical abstract: Abstract: This paper aims to present retrofit and design methodologies for building frames using target energy as design criteria for passive dampers. Initially, a damper design methodology based on the energy balance concept is discussed and applied to retrofit buildings: under-designed, requiring seismic up-gradation. Furthermore, a methodology is presented for the seismic design of a new building with passive dampers. The proposed methods were applied to reinforced concrete (RC) frames with and without vertical irregularities. The design of these frames with dampers is verified using nonlinear time history analysis considering spectrum compatible near-field and far-field recorded ground accelerograms. The damping constants obtained from the proposed methodology are compared to those calculated using the FEMA 356 method. The response results indicate that the proposed methodologies effectively enhance the RC frame seismic performance for a given seismic hazard level. The proposed methods find their application to the design offices where damper design can be carried out using design spreadsheets developed while avoiding iterations in determining damping constants.